Features of Absolutist Doctrine in Robert Filmer’s “Patriarcha” - A. V. Zhuravlev (Научный диалог, 2017)
The article is devoted to analysis of the role of natural law doctrine in the justification of the absolutism by the English thinker Robert Filmer (1588-1653). On the material of his key political work “Patriarcha” it is shown that the appeal to natural law takes in Filmer’s theory a place no less important than using patriarchal arguments. The main feature of the variant of absolutist ideology proposed by Filmer was a denial of the contractual origin of society, at the same time compatible with the reliance on natural law arguments. The paper focuses on his interpretation of the origin of monarchical power, the interpretation of the English legal system and the role of the monarch as the only Supreme lawgiver, and also the interpretation of the questions of the origin of property rights. The article demonstrates that in Filmer’s patriarchal interpretation the society from an entity made up of autonomous individuals, turns into a natural unity, where the people remain in constant dependence on their parents and, in the end, on the power of the “Supreme father,” personified by the figure of the reigning monarch. Since royal power is based directly on natural law, subjects are unable to put forward any constitutional limits on the power of the king.